Detective looking chart: plutchik emotion games for kids through VARK Model for ASD children - Hassan, Muhamad Hafiz; Wardi, Rainal Hidayat; Mohd Razali, Noraziah; Hishamuddin, Nurul Amy Azura; Toha@Tohara, Abdul Jalil; Ahmad, Muhammad Fakhruddin; Jimel, Clement (Universiti Teknologi Mara, Kedah, 2022)
The visual teaching resources utilized to support children with Autism Spectrum Disorder (ASD) from the perspective of the ASD instructors were investigated in this study by using the qualitative research approach. Besides, realizing the development of a teaching aid for children with ASD by implementing the VARK Model of learning styles based on four main types of learners: visual, auditory, reading/writing, and kinesthetic. In addition, the construction of this game board is based on the idea that ASD children can express emotions based on Plutchik's wheel theory, which highlights emotions that help ASD children visualize the spectrum of emotions and how they relate to each other. Besides, this innovation can be linked to the development and behavioural interventions for ASD in shaping learning that affects cognitive and affective aspects.